Saccharomyces cerevisiae Catalyzed Synthesis and Evaluation of Pyrazoles - Rajkumar, Thangavelu; Venkata, Suresh Kumar Solleti; Nagarajan, Srinivasan (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Biocatalysis in organic solvents has several benefits over aqueous solvents, including solubility of organic substrates, ease of workup, separation of the product, and, in certain cases, reusability of biocatalysts. Materials and Methods: A simple, effective, and environmentally friendly technique for synthesizing pyrazoles has been established, which involves the cyclo condensation of chalcones and isonicotinic acid hydrazide in organic solvents using a relatively inexpensive catalyst baker’s yeast (Saccharomyces cerevisiae). Molecular properties prediction and docking studies were also performed. Results: The predicted molecular properties suggest that the molecules are safe for oral consumption and their docking studies on 2BVC-Mycobacterium tuberculosis glutamine synthetase show their favorable ligand binding nature. The structural assignments were validated based on spectrum data. The compounds were evaluated for their antitubercular, in vitro anti-inflammatory, and anti-oxidant effects. The analysis reveals that synthesized derivatives of pyrazoles possessing methoxy, nitro, hydroxyl, fluoro, and chloro substitution through the phenyl ring help the molecule to increase its pharmacological activities. However, the substituted thiophene ring in the side chain also facilitates the biological action of the molecules. Conclusion: Anti-inflammatory, anti-oxidant, and anti-tubercular properties are due to the presence of the pyrazole ring.
Keywords: Pyrazoles; Chalcones; Saccharomyces cerevisiae; In vitro Anti-inflammatory; Antioxidant; Anti-tubercular